Badanie potrzeb językowych studentów zza wschodniej granicy. Implikacje dydaktyczne dla praktycznej nauki języka na kierunku Studia polskie dla cudzoziemców - Wawrzeń, Marzena (Neofilolog, 2024)
In the academic year 2022/2023, the Faculty of Polish Studies of the Jagiellonian University opened Polish studies for foreigners, which enables learning the Polish language as part of university education. Due to the growing number of students from Ukraine, the goals, effects and content of teaching in this field should be transformed to meet the specific linguistic needs of students from beyond the eastern border. The aim of the article is to present the teaching goals and priorities of students from Ukraine. The results of the study will be compared with the teaching rules of the contemporary methodology of teaching Polish as a foreign language to Eastern Slavs.